Peter Pan in Mummy Land : a graphic novel - Harper, Benjamin; Cano, Fernando (Stone Arch Books, a Capstone imprint, 2020)
Claiming he is tired of "kid stuff," Peter Pan wraps himself in bandages and moves his friends to Mummy Land, but when Wendy points out that pretending to be something you are not is exactly what kids do, the Dust Boys decide to return to the real world with her--if they can escape from the skeleton Captain Hook.
Includes notes on the original story of Peter Pan.
Ages 8-12.
Keywords: Peter Pan -- (Fictitious character) -- Comic books, strips, etc; Peter Pan -- (Fictitious character) -- Juvenile fiction; Hook, -- Captain (Fictitious character) -- Comic books, strips, etc; Hook, -- Captain (Fictitious character) -- Juvenile fiction; Mummies -- Comic books, strips, etc; Mummies -- Juvenile fiction; Pirates -- Comic books, strips, etc; Pirates -- Juvenile fiction; Graphic novels; Graphic novels; Mummies -- Fiction; Pirates -- Fiction; Graphic novels